CORRELATION AMONG READING INTEREST, READING HABIT, READING MOTIVATION AND READING COMPREHENSION ACHIEVEMENT OF THE ELEVENTH GRADE STUDENTS OF STATE HIGH SCHOOL 7 OF PRABUMULIH - Erni Sarwinda (Universitas PGRI Palembang, 2019)
AbstractThis was concerned with the inquiry on the correlation among reading interest, reading habit, reading motivation and reading comprehension achievement of the Eleventh Grade Sudents of State High School 7 of Prabumulih. The problem of this study was to find out whether or not there are significant correlations among reading interest, reading habit, reading motivation and reading comprehension of the Eleventh Grade Sudents of State High School 7 of Prabumulih. Data collection is deliberated by using questionnaire. validity test, normality test, homogeneity test, linearity test, Data analyse used r- product moment and multiple regression. Findingshowed that there was significant correlation among reading interest, reading habit, reading motivation and reading comprehension achievement of theEleventh Grade Sudents of State High School 7 of Prabumulih. Conclusion suggests that there are significant correlation among reading interest, reading habit, reading motivation and reading comprehension achievement of the Eleventh Grade Sudents of State High School 7 of Prabumulih.Keywords: Reading Interest, Reading Habit, Reading Motivation, and Reading Comprehension Achievement